Transfusion Requirements in ESRD Patients Admitted with GI Hemorrhage Undergoing Inpatient Endoscopy. Issue 12 (December 2016) - McCartney, Conor; Santosh, Shrihari; Patolia, Setu; Santosh, Sadashiv
Abstract : Objectives: To date there are no studies evaluating the utilization of blood products in patients with end-stage renal disease (ESRD) with gastrointestinal (GI) hemorrhage. This study estimated transfusion needs and determined predictors available at the time of admission for patients with ESRD admitted to a university hospital with GI bleeding requiring inpatient endoscopy. Methods: A retrospective chart review was performed on all patients with ESRD who underwent inpatient endoscopy for suspected GI bleeding between 2009 and 2015. Results: Ninety-nine hospital admissions from 76 patients met the inclusion criteria. Patients received mean 2.9 ± 2.6 red blood cell (RBC) units. In the multivariate analysis, increased prothrombin time, low initial hemoglobin, admission to intensive care unit, congestive heart failure, white race ( P = 0.08), and syncope ( P = 0.09) were independent predictors of RBC transfusion. A total of 28% received fresh frozen plasma and 8% received platelets. Prolonged prothrombin time was the only independent predictor of fresh frozen plasma transfusion ( P < 0.001). Platelet transfusion was predicted by thrombocytopenia at platelet counts <100, 000/mm 3 ( P < 0.001) and white race. Coronary artery disease was associated with reduced platelet transfusion. Other baseline comorbidities, bleeding source, and active/recent hemorrhage on endoscopy did not predict transfusion. Desmopressin use was not associated with reduced RBC needs, even after adjusting for other covariates. Ninety-seven percent of patients survived to discharge. Conclusions: Patients with ESRD admitted to the hospital with GI bleeding have high blood transfusion requirements, which are predicted by variables available at the time of admission. Rockall score and most other predictors of mortality did not predict transfusion.